THE CASE FOR FULLY-FLEDGED PROFIT-LOSS SHARING BANKING - Mohammad Said Fathurrohman (Universitas Airlangga, 2020)
The original idea of Islamic banking is a two-tier profit-loss sharing banking.However, in practice Islamic banking only implements profit sharing in its funding side, while on the financing side profit sharing only take smaller share than that of fixed return financing, which is predominantly sale-basedfinancing. This paper aims to examine examine the issues in debt-like financing that are commonly used by Islamic banking. There are issues with the shariah validity of these types of financing due to involving multiple contracts. The issues in multiple contracts have economic implications, including risks and value added, which provide economic reasons to validate profit. Analysis on multiple contracts shows some conflict of rights and obligation implied by different contracts which are combined to form murabahah financing and musharakah mutanaqisah. The benefit analysis shows that both salebased financing and interest-paying credit takes profit from buyer for providing benefit of deferred payment. There is no real benefit of sale-based or rent-based financing for customer since Islamic banks never run real trading or rental business. This paper recommends Islamic banking to focus on its core as profit-sharing banking. Finally, this paper discusses some problems facing Islamic banking on the way transforming itself into fully-fledged profit-loss sharing banking and offers ideas to resolve it.